The Relationship Between Household Drinking Water Quality and The Incidence of Stunting - Deli Syaputri; Theodorus Teddy Bambang Soedjadi; Samuel Marganda Halomoan Manalu; Risnawati Tanjung; Devi Rosana (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Unhealthy housing conditions will hurt human health, one of which is ARI. Based on data from the Stabat Health Center, ARI is among the top 10 diseases. Based on 2019 data, there were 1572 cases; the increase in cases occurred from 2020 to 1692, with 206 cases in Sidomulyo Village. Moreover, the physical condition of the houses in Sidomulyo still needs to meet the requirements of a healthy home. Based on the Basic Health Research (Riskesdas) report, the prevalence of stunting in Indonesia increased from 2016 to 2018, namely 27.5% in 2016, 29.6% in 2017, and 30.8% in 2018 (Riskesdas, 2018). Factors causing stunting are divided into direct causal factors and indirect causal factors. This study aimed to determine the relationship between household drinking water quality and the incidence of stunting in children aged 6-59. Observational research with a case-control design on children aged 6-59 months in the Talun Kenas Health Center Area, Deli Serdang Regency. The sampling technique was carried out by consecutive sampling with a total sample of 42 subjects in each group. Stunting was categorized based on TB/U score < -2 SD according to KEPMENKES RI anthropometric standard table. Drinking water quality was tested using a sanitarian kit—bivariate analysis using the Chi-Square test by looking at the Odds Ratio (OR). The results of the bivariate analysis show that the quality of household drinking water is associated with stunting in children aged 6-59 months (p=0.004; OR=4.144), meaning that the quality of drinking water that does not meet the requirements increases the incidence of stunting in children aged 6-59 months. This study concludes a significant relationship between the quality of household drinking water and the incidence of stunting in children aged 6-59 months.